The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1002/lt.26103
|View full text |Cite
|
Sign up to set email alerts
|

Cannabinoid Use Among Liver Transplant Recipients

Abstract: The effect of cannabinoids on liver transplant outcomes is an area of active research. We aimed to investigate marijuana (MJ) and cannabidiol (CBD) use among liver transplant recipients at the University of Colorado Hospital (UCH), specifically prevalence, habits, and predictors of use. Liver transplant recipients followed at UCH with valid email addresses were sent an informed consent postcard and survey invitation. This exploratory survey was conducted using REDCap. IBM SPSS Statistics software was used for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 41 publications
0
16
0
Order By: Relevance
“…A survey study showed that self-reported physical health ratings were not significantly different among post-transplantation marijuana users, former marijuana users, and non-users (3). Self-reported mental health ratings were worse among post-transplantation marijuana users as compared to former users and non-users, although it is not known if this was directly due to marijuana use or if self-perceived worse mental health resulted in marijuana use (3). We note, however, that the designs of the above studies are subject to selection and reporting biases (3,28).…”
Section: Impact Of Pre-transplantation and Posttransplantation Mariju...mentioning
confidence: 81%
See 2 more Smart Citations
“…A survey study showed that self-reported physical health ratings were not significantly different among post-transplantation marijuana users, former marijuana users, and non-users (3). Self-reported mental health ratings were worse among post-transplantation marijuana users as compared to former users and non-users, although it is not known if this was directly due to marijuana use or if self-perceived worse mental health resulted in marijuana use (3). We note, however, that the designs of the above studies are subject to selection and reporting biases (3,28).…”
Section: Impact Of Pre-transplantation and Posttransplantation Mariju...mentioning
confidence: 81%
“…Self-reported mental health ratings were worse among post-transplantation marijuana users as compared to former users and non-users, although it is not known if this was directly due to marijuana use or if self-perceived worse mental health resulted in marijuana use (3). We note, however, that the designs of the above studies are subject to selection and reporting biases (3,28). Also, important factors like the route of marijuana administration, the quantity of marijuana use, and toxicology screens were not determined and included in the analysis (28).…”
Section: Impact Of Pre-transplantation and Posttransplantation Mariju...mentioning
confidence: 99%
See 1 more Smart Citation
“…Cannabinoids are among the most controversial topics that SOT clinicians encounter [22] as their use continues to rapidly gain widespread legal and societal acceptance. Use is similarly increasing among liver transplantation patients with 12-month cannabis use rates in candidates at 11.0% and recipient rates of active cannabis use of 23.8% and rates of active cannabidiol use of 21.0% [23,24 ▪ ]. Cannabinoid data in SOT exist primarily in liver and kidney populations and less is known about their effects in heart and lung candidates and recipients.…”
Section: Cannabinoid Usementioning
confidence: 99%
“…[1,2] Cannabinoids Social, legal, and medical landscapes of cannabinoid use are rapidly evolving in the United States, and LT policies are similarly heterogenous. [8] Cannabinoid use is increasing in LT patients, [18,19] and there is no expert consensus regarding cannabinoid use in LT despite the numerous medical and psychosocial considerations of which clinicians must be aware including possible drug interactions with immunosuppressants. [20] A minority of LT programs allow active marijuana use in their candidates.…”
Section: Substance Use Alcoholmentioning
confidence: 99%